Review of Summer School Mathematics Framework Program - Merva Kurd (The Indonesian Institute of Science and Technology Research, 2023)
In the summer school mathematics framework program, which is prepared while the materials deemed necessary to be used in the teaching process in the programs prepared to date are left to the opinion of the teacher and more concrete materials are used, the digital materials proposed to be used by the teachers in this process are prepared in accordance with the achievements and are included in the program as ready for which goals they will be used. In this context, the aim of the study is to examine the materials in the summer school mathematics framework program prepared to be implemented in the summer school in 2022 and so to evaluate them in terms of their suitability for the goals. In this study, document review method, which is one of the qualitative research methods, was used. The research data were obtained by examining the digital materials in the summer school mathematics framework program prepared for middle schools. When the summer school mathematics framework program and the materials of the program in the learning process in this program are examined, it is revealed that the focus is on mathematics and the e-contents related to the field in the EBA application are included under the title of learning processes in this program and the program is supported by the use of digital materials.